Examine The Concept of Forgiveness in Juvenile Cases as Per Article 70 of The Judicial System Act Regarding Children's Criminal Responsibility - Mashendra (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
This paper aims to explore the meaning of forgiveness of judges set out in Article 70 Law No. 11 of 2012 on juvenile criminal justice system (SPPA). When examined further, the explanation of Article 70 of the law only contains the word”self-explanatory